2018
DOI: 10.1002/osp4.142
|View full text |Cite
|
Sign up to set email alerts
|

Together Eating & Activity Matters (TEAM): results of a pilot randomized‐clinical trial of a spousal support weight loss intervention for Black men

Abstract: SummaryObjectivesThe objective of this study is to evaluate the feasibility, participation, preliminary efficacy and retention in a couples‐based weight loss intervention among Black men.Design, setting, participantsTwo‐arm pilot randomized clinical trial in an academic clinical setting. Forty self‐identified Black men and their female cohabitating partners (n = 80) aged 18 to 65 years with body mass index from 25 to 45 kg/m2 were randomized using computer generated tables to allocate treatments.InterventionPa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 32 publications
(49 reference statements)
0
9
0
Order By: Relevance
“…The current report suggests that daily self‐weighing has potential for good uptake among minority men and women, and the behavior promotes successful weight loss in some subgroups, particularly African American men and women with diabetes. Other intervention studies have reported low rates of self‐weighing among African American men , suggesting more detailed exploration of this practice may be warranted.…”
Section: Discussionmentioning
confidence: 99%
“…The current report suggests that daily self‐weighing has potential for good uptake among minority men and women, and the behavior promotes successful weight loss in some subgroups, particularly African American men and women with diabetes. Other intervention studies have reported low rates of self‐weighing among African American men , suggesting more detailed exploration of this practice may be warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Ten studies completed longer term follow‐up measures with participants (12–24 m: n = 6; >24 m: n = 4) 33,38,39,65–71 . Twenty studies were pilot or feasibility studies 33,35,37,38,65,72–86 . Weight loss was the main intervention outcome in most studies ( n = 28), with maintenance of weight lost the focus in two trials 66,67 .…”
Section: Resultsmentioning
confidence: 99%
“…Two of these studies were of the Healthy Dads Healthy Kids intervention in Australia, 37,88 and two were of cultural adaptations of the same program in the UK 77 and the USA 82 . One study examined the effects of a group‐based intervention with and without spousal support in African American men 72 . All other studies involved only men.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations